Sustainable biocomposites from renewable resources inWest Africa: A review - (:unkn) unknown (My University, 2025)
The use of agricultural residues in biocomposite production has gained increasing attention, driven by several benefits. Converting agricultural by-products into bio-based materials within a circular economy represents a sustainable strategy to mitigate lignocellulosic waste, reduce reliance on fossil resources, and lower environmental pollution. This approach also creates economic opportunities for rural African communities by generating diverse income sources for workers in collection, processing, and manufacturing. As a result, the integration of agricultural residues into biocomposites production not only addresses environmental concerns but also fosters economic growth and supports rural development. In this review, five biomasses from West Africa are examined, focusing on their production, chemical composition, physical and mechanical properties, and potential applications in biocomposites. The five biomasses listed are cocoa pod husks, oil palm empty fruit bunches, rice husks, millet stalks, and typha stalks. Key parameters, such as the type of binder, fiber dimensions, fiber-to-binder ratio, and the strength of fiber-binder adhesion, are systematically studied to assess their influence on the overall performance of the resulting composites. Special attention is given to understanding how these factors affect mechanical properties (e.g., strength and flexibility), thermal behavior (e.g., insulation capacity and heat resistance), and physico-chemical characteristics (e.g., moisture absorption, density, and chemical stability). This comprehensive analysis provides insights into optimizing composite formulations for enhanced functionality and sustainability. This study is essential to optimize the use of agricultural residues in West Africa for biocomposites, tackling waste issues, promoting sustainability, and filling research gaps on their properties.
Keywords: African Research